Web-Based Employee Attendance Application at the Youth and Sports Department of North Sumatra Province - Nugroho, Bagus; Annabil, Muhammad Haziq (Journal of Computer Science and Informatics Engineering, 2023)
Advances in information technology play a key role in shaping and managing daily activities. The effect of increasingly modern technology is that it makes it easier for users to process information. Even so, the Youth and Sports Service agency still processes data, namely employee attendance, manually, namely collecting data on attendance letters. This research aims to build a web-based employee attendance application to create a fast and integrated information system. The method used is data collection. In this method the author carried out observations, interviews and also looked for studies related to this research. Then the author analyzes the data that has been obtained, then the author designs the application and tests it using the black box testing method. The results of this research are in the form of an employee attendance data application which is currently implemented in a computerized and timely manner in terms of recording employee attendance data from the North Sumatra Dispora because the attendance process no longer requires available books or archives.